DIRECT COST OF HEMODIALYSIS IN AN ADULT INTENSIVE CARE UNIT - Jony Hsiao; Antônio Fernandes Costa Lima (Universidade Federal do Paraná, 2015)
The present study aimed to identify the average direct cost of conventional hemodialysis performed by nursing technicians on patients with acute kidney injury in Adult Intensive Care Unit. Quantitative analysis in case study research conducted in a public teaching and research hospital, between January and April 2014. The average direct cost of the stages of hemodialysis was calculated by multiplying the time needed to perform the procedure by the unit cost of direct labor and adding this value to the cost of materials, solutions and drugs. The total direct cost obtained was R$ 434,83 (SD= 65.10), which was impacted by the average direct costs of the "monitoring" steps" (R$ 205,58), "preparation of the machine and extracorporeal circuit" (R$ 120,96) and "internal disinfection and machine cleaning" (R$ 42,10). It is concluded that the proposed methodology can be reproduced in other Intensive Care Units to assist in the decision making regarding allocative efficiency of the resources involved in the procedure of conventional.